2021
DOI: 10.1016/j.jvs.2020.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Double fenestrated physician-modified stent-grafts for total aortic arch repair in 50 patients

Abstract: Objective: Our aim was to evaluate the early-and medium-term outcomes of using double fenestrated physicianmodified endovascular grafts (PMEGs) for total endovascular aortic arch repair.Methods: The present single-center retrospective analysis of prospectively collected data included 50 patients from January 2017 through October 2019, who had undergone thoracic endovascular aortic repair (TEVAR). The fenestrations were a proximal larger fenestration that incorporated the brachiocephalic trunk and left common c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The same research team recently reported on a series of 50 patients receiving double-fenestrated physician-modified stent grafts to preserve all supra-aortic branches. [43] The outcomes were similarly satisfactory: the prevalence of technical success was 94%, type-II endoleak was 4%, 30-day mortality was 2%, and reintervention was 8%. Zhang et al [44] conducted a comparative study of physician-modified fenestration (110 cases) and chimney technique (364 cases).…”
Section: Fenestration Techniquementioning
confidence: 89%
“…The same research team recently reported on a series of 50 patients receiving double-fenestrated physician-modified stent grafts to preserve all supra-aortic branches. [43] The outcomes were similarly satisfactory: the prevalence of technical success was 94%, type-II endoleak was 4%, 30-day mortality was 2%, and reintervention was 8%. Zhang et al [44] conducted a comparative study of physician-modified fenestration (110 cases) and chimney technique (364 cases).…”
Section: Fenestration Techniquementioning
confidence: 89%
“…A pre-loaded guidewire has been recommended to assist in overcoming the migration ( 21 ). Chassin-Trubert et al reported improvement in the success rate after applying the pre-loaded guidewire [from 94% (19/22) to 100% (28/28)], all of which were total endovascular aortic arch repair, revascularizing all supra-aortic trunks ( 22 ). Additionally, the alignment could be simplified and reassured with a pre-loaded guidewire, thus shortening the learning curve ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many technical challenges to endovascular repair in the aortic arch (i.e., curvature, angulation, short distance of the landing neck, hemodynamics, and respiratory motion), bifurcated custom SGs have gained acceptance over the past decade. 14…”
Section: Discussionmentioning
confidence: 99%